2014
DOI: 10.1017/jns.2014.25
|View full text |Cite
|
Sign up to set email alerts
|

Owner misperception of canine body condition persists despite use of a body condition score chart

Abstract: Canine obesity is a prevalent disease, but many owners are unaware of it, partly due to misperception of their dog's body shape. Body condition scoring (BCS) is a simple method of assessing body composition, but whether it can reduce owner misperception is unclear. Our aim was to determine the effect of a BCS system on owners' ability to estimate the body condition of their dog. Information from 110 dog owners attending three UK veterinary practices was gathered, by interview, between March and April 2013. Fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
77
5
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(94 citation statements)
references
References 20 publications
11
77
5
1
Order By: Relevance
“…Indeed, while owners of underweight dogs do tend to overestimate the condition of their dog, the effect is less marked than the tendency for owners of overweight dogs to underestimate the condition (Eastland-Jones and others 2014). Clearly, therefore, more effort is required to educate owners, breeders and show judges so that they can all better recognise overweight condition.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, while owners of underweight dogs do tend to overestimate the condition of their dog, the effect is less marked than the tendency for owners of overweight dogs to underestimate the condition (Eastland-Jones and others 2014). Clearly, therefore, more effort is required to educate owners, breeders and show judges so that they can all better recognise overweight condition.…”
Section: Discussionmentioning
confidence: 98%
“…Limitations of this investigation include the use of owner assessment of BCS and owner report of other questionnaire items; prior studies have shown that owners inaccurately report body condition (34). However, we validated the use of BCS in this sample by cross-referencing BCS against ownerreported current-to-ideal body weight ratios and identified significant overlap as detailed in Methods.…”
Section: Discussionmentioning
confidence: 99%
“…For the purposes of this analysis, we grouped the six pictures into four categories: underweight (corresponding to BCS 3 or lower); ideal (corresponding to BCS 4-5); overweight (corresponding to BCS 6); and obese (corresponding to BCS 7 or higher). Since owners have been reported to systematically misperceive body condition scores (34) we validated these scores against current and ideal body weights reported by a subset of respondents. Owner-reported BCS showed strong correspondence with owner-reported current-to-ideal body weight ratios.…”
Section: Overweightness and Obesitymentioning
confidence: 99%
“…Despite the such as cardiorespiratory diseases (Ettinger & Feldman, existence of many methods, the owner's perception about 1995), osteoarthritis (Impellizeri et al, 2000), chronic the body condition of their canine companion plays a http://doi.org/10.4038/slvj.v63i2.11 significant role to maintain an ideal BC. Some studies conducted in UK revealed that under estimation of BC in pet dogs is quite common among the dog owners (Courcier et al, 2009;Eastland-Jones et al, 2014). Research to investigate the causes of misperception is important to maintain a healthy and ideal dog.…”
Section: Introductionmentioning
confidence: 99%